(untitled) (Journal of the College of Education for Women, 2018)
Terrorism is a global phenomenon that engulfs most regions of the world to varying degrees. Media outlets are aware of the many incidents of violence and terrorism that have increased in recent times. The differences between the size of the phenomenon in different societies are the causes and severity of the phenomenon. On the role of local satellite channels in shaping the knowledge and trends of the Iraqi public towards the events of terrorism, in light of the assumptions of reliance on the media. The importance of this study is that it assesses the role of local satellite channels in the formation of knowledge and trends The study seeks to know the extent of exposure of the Iraqi public to local satellite channels, and to reveal the extent of the Iraqi public’s knowledge of the concept and issues of terrorism and to measure the effects of demographic variables on the levels of knowledge and trends of the public The study found that respondents are exposed daily to local satellite channels and spend different time periods in their exposure to these channels. The study revealed the keenness of the respondents to follow up the television articles and programs dealing with the issues of terrorism Hap.